Analysis of Toxoplasma gondii Repeat Region 529 bp (NCBI Acc. No. AF146527) as a Probe Candidate for Molecular Diagnosis of Toxoplasmosis - Dyah Ayu Oktavianie A Pratama; S. Sumartono; Wayan T. Artama (Indonesian Journal of Biotechnology, 2009)
Toxoplasmosis is a disease caused by protozoan parasite Toxoplasma gondii. The infection is commonly asymptomatic. The availability of confirmative and accurate detection system is really needed. This research was aimed to develop a molecular diagnosis based on the conserved and high copy number repeat region of Toxoplasma gondii with hibridization method. Nucleic acid was isolated from tachyzoites. The repeat region of T. gondii was amplified using PuRe Taq Ready To Go-PCR Beads (Amersham Bioscience),  forward primer 5’- GAC TCG GGC CCA GCT GCG  -3’ and reverse primer 5’- CCT CTC CTA CCC CTC CTC -3’. The amplicon was sequenced using ABI Prism 3100-Avant Genetic Analyzer (PT. Charoen Pokphand, Jakarta). Probe was labeled using digoxigenin-11-dUTP. Application of probe to detect it’s complementary nucloeic acid was done by hibridization method.The research concluded that probe toxo-103 bp was highly homolog with several strain of T. gondii and it has no homology either with host’s genome or other parasites which have close genetic relationship with T. gondii.   Hybridization analysis showed that probe could detect the complementary nucleic acid up to 10 ng/ul concentration.